2016
DOI: 10.1111/jop.12440
|View full text |Cite
|
Sign up to set email alerts
|

PI3K–AKTmTOR pathway proteins are differently expressed in oral carcinogenesis

Abstract: Our study demonstrated higher pAKT and pmTOR expression during carcinogenesis of oral mucosa, differing considerably among OED and OSCC specimens when compared to NDOT. These proteins can be considered potential diagnostic markers for early detection of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
(65 reference statements)
6
32
0
2
Order By: Relevance
“…Accordingly, in the context of OSCC, mTOR activation has also been reported in the vast majority of cases. Martins et al found mTOR activation in 77.4% of cases, and herein we detected over 80%. This highlights the relevance of this pathway as a promising therapeutic target for pharmacological intervention in HNSCC .…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Accordingly, in the context of OSCC, mTOR activation has also been reported in the vast majority of cases. Martins et al found mTOR activation in 77.4% of cases, and herein we detected over 80%. This highlights the relevance of this pathway as a promising therapeutic target for pharmacological intervention in HNSCC .…”
Section: Discussionsupporting
confidence: 62%
“…Chaisuparat et al reported S6 phosphorylation in 100% of oral epithelial dysplasias, and in 88.67% of OSCC, indicating that S6 phosphorylation is active in early stages of oral tumorigenesis. In line with these findings, Martins et al studied the expression pattern of several components of the PI3K‐AKT‐mTOR pathway in hyperkeratotic oral mucosa, oral epithelial dysplasia, and OSCC, and found that the percentages of cases with phosphorylated S6 were 52.9%, 70.8%, and 77.4%, respectively. In good agreement with these data, our findings show a high prevalence of S6 phosphorylation in OSCC specimens higher than 80%.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations